Starch granule initiation is controlled by a heteromultimeric isoamylase in potato tubers - Bustos, Regla (National Academy of Sciences, 2004)
Starch granule initiation is not understood, but recent evidence implicates a starch debranching enzyme, isoamylase, in the control of this process. Potato tubers contain isoamylase activity attributable to a heteromultimeric protein containing Stisa1 and Stisa2, the products of two of the three isoamylase genes of potato. To discover whether this enzyme is involved in starch granule initiation, activity was reduced by expression of antisense RNA for Stisa1 or Stisa2. Transgenic tubers accumulated a small amount of a soluble glucan, similar in structure to the phytoglycogen of cereal, Arabidopsis, and Chlamydomonas mutants lacking isoamylase. The major effect, however, was on the number of starch granules. Transgenic tubers accumulated large numbers of tiny granules not seen in normal tubers. These data indicate that the heteromultimeric isoamylase functions during starch synthesis to suppress the initiation of glucan molecules in the plastid stroma that would otherwise crystallize to nucleate new starch granules.